Variability in Sex Assignment at Birth and Etiological Diagnosis of Differences of Sex Development: A Ten-Year Institutional Experience from Assam - Praveen Nagarajaiah; Ashok K Bhuyan; Abhamoni Baro; Uma K Saikia (Indian Journal of Endocrinology and Metabolism)
Introduction: Differences of sex development (DSD) also known as disorders of sex development encompass a wide spectrum of conditions with varying clinical presentations across different age groups. This study aims to analyse various aetiologies of DSD in Assam and the variability of sex assignment at birth.